Influence of multilayer Al-doped ZnO thin film on photocatalytic degradation of methyl blue - Liszulfah Roza,; Vivi Fauzia,; Mohd. Yusri Abd. Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The present work is focused on the photocatalytic activities of Al-doped ZnO sample deposited with different layers on glass substrate. The Al-doped ZnO sample was prepared via simple and cost effectiveness chemical precipitation method with addition of 5 wt. % of Aluminum chloride as dopant. All materials were dissolved in mixture of 45 mL ethylene glycol and 15 mL deionized water while the growth process was carried out at temperature 200 °C for 30 min assisted with stirring process at 550 rpm using hotplate. The precipitated of as prepared sample were deposited with different layers on glass substrate using spin coating process. The samples were characterized by UV-Vis spectrophotometer, Raman spectroscopy, and photoluminescence to investigate the optical properties and crystal structure of ZnO sample. In particular, according to UV-Vis the absorption spectra of the sample significantly increase as the number of layers increase. Meanwhile, Raman and photoluminescence analysis indicate that the sample contains lots of structural defect as a result of the incorporation of ion Al into ZnO lattice. The photocatalytic activity of Al-doped ZnO thin film with different layers was evaluated in degradation of methyl blue solution under UV light illumination. The best photocatalytic activity was observed from 6 layers of Al-doped ZnO thin film within 45 min of exposure to UV light illumination. This study may open a versatile route to achieving high efficiency of photocatalytic activity of ZnO.